2000
DOI: 10.1038/sj.onc.1203652
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative induction of mammary tumorigenesis by TGFα and Wnts

Abstract: We previously reported that multiparous WAP-TGFa transgenic mice develop mammary gland carcinomas with complete incidence. TGFa-induced tumors appear stochastically and with relatively long latency, indicating an additional requirement for other genetic alterations. To identify genes that cooperate with TGFa in mammary tumorigenesis, we used a retroviral insertion approach featuring a cloned and infectious hybrid MMTV (C3H/ Mtv-1; (Shackleford and Varmus, 1988)). Tumor latency was decreased approximately 30% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Wnt and EGFR signaling activities have important functional roles in a wide range of biological processes, from developmental fate decisions to neoplasia. These signaling pathways can act antagonistically as in Drosophila larval cuticle development (24) or cooperatively as in mouse mammary tumor formation (25). Civenni et al have reported that Wnt conditioned medium can activate the EGFR by a metalloprotease-dependent release of EGFR ligands in a manner analogous to GPCR transactivation of the EGFR (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt and EGFR signaling activities have important functional roles in a wide range of biological processes, from developmental fate decisions to neoplasia. These signaling pathways can act antagonistically as in Drosophila larval cuticle development (24) or cooperatively as in mouse mammary tumor formation (25). Civenni et al have reported that Wnt conditioned medium can activate the EGFR by a metalloprotease-dependent release of EGFR ligands in a manner analogous to GPCR transactivation of the EGFR (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Glands-Previous studies have demonstrated a functional relationship between ␤-catenin and EGFR in tumor progression (9,16). We therefore analyzed our tumor and mammary gland samples to determine if the 180-kDa kinase we had detected immunoprecipitating with ␤-catenin ( Fig.…”
Section: Egfr and C-neu Associate With ␤-Catenin In Tumors But Not Nomentioning
confidence: 99%
“…Is Tyrosine-phosphorylated in MMTV-Wnt-1 Tumors-EGFR-induced tumor formation in the mammary gland is promoted by cooperative events with Wnt-mediated signaling, since both Wnt-1 and Wnt-3 were found to be up-regulated in tumor samples from WAP-TGF␣ transgenic animals (9). To directly examine the role of EGFR signaling in Wnt-1-mediated tumorigenesis, we utilized the MMTV-Wnt-1 transgenic mouse (19).…”
Section: ␤-Cateninmentioning
confidence: 99%
See 1 more Smart Citation
“…When wnt-1 or int-2 was targeted to the mammary gland of transgenic mice, wnt-1 was highly tumorigenic in females whereas int-2 was weakly tumorigenic; the two oncogenes acted synergistically in doubly transgenic animals (Kwan et al, 1992). It has been shown recently that wnt-1 can also cooperate with TGFa in transgenic animals (Schroeder et al, 2000).…”
Section: Introductionmentioning
confidence: 99%